Pengaruh Pop Up Book terhadap Kemampuan Membaca Permulaan pada Peserta Didik Usia Sekolah Dasar - Lailatussyifa Lailatussyifa; Rina Devianty; Muhammad Syaifullah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research is entitled "Influence Pop Up Book on Beginning Reading Ability in Elementary School Age Students”. This research was conducted to determine the effect of pop up book on the initial reading ability of elementary school age students. This research is quantitative research with a quasi-experimental or quasi-experimental research design with non equivalent control group design. The population in this study were class I MIN 2 South Labuhanbatu students. The samples in this research were taken using techniques purposive sampling as many as two classes, namely class I-A with 26 students, are taught using media pop up book as an experimental class while class I-B with 26 students was taught using conventional learning as a control class. The data was analyzed using a normality test, a homogeneity test to determine whether the data for the two samples were normally and homogeneously distributed, then a t test to determine the effect of learning media on students' initial reading ability with the help of the SPSS 20 application. The results of data analysis showed that the sig. (2-tailed) is 0.001 0.05 so that Ho is rejected and Ha is accepted, indicating that there is an influence pop up book on the initial reading ability of elementary school age students in class I MIN 2 South Labuhanbatu.